A scoping review of metaverse-facilitated child sexual abuse - Nichola Copson; Shane D. Johnson (Social Sciences and Humanities Open, 2025)
This scoping review investigated the complexities of child sexual abuse that is or could be facilitated by the metaverse. Following the PRISMA-ScR (Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews) guidelines, and synthesising insights from 28 diverse sources, it systematically maps existing threats, uncovers gaps in knowledge, and outlines potential solutions. The review provides a narrative analysis of the available evidence related to potential metaverse victims, offenders, virtual depictions, associated threats, and mitigation strategies. The findings highlight grooming, child sexual abuse, and the distribution of abusive materials as the primary threats within these immersive environments. Suggested countermeasures include stricter age-based platform regulations, enhanced collaboration between law enforcement agencies and bystanders, and the use of advanced artificial intelligence to detect and prevent abuse. Concerns also emerged about the metaverse potentially normalising and desensitising abusive behaviours, which could escalate into physical acts of abuse. Overall, the review highlights the need for more scholarly research and proactive interventions to address the technological and human factors in metaverse-facilitated child sexual abuse.